2020
DOI: 10.1038/s41598-020-77792-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical hypoxia induces apoptosis of human pluripotent stem cells by a NOXA-mediated HIF-1α and HIF-2α independent mechanism

Abstract: Human embryonic and induced pluripotent stem cells (hESCs and hiPSCs) are self-renewing human pluripotent stem cells (hPSCs) that can differentiate to a wide range of specialized cells. Notably, hPSCs enhance their undifferentiated state and self-renewal properties in hypoxia (5% O2). Although thoroughly analyzed, hypoxia implication in hPSCs death is not fully determined. In order to evaluate the effect of chemically mimicked hypoxia on hPSCs cell survival, we analyzed changes in cell viability and several as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…hPSCs are very susceptible to undergo apoptosis due to their higher state of mitochondrial priming, a lowered cell intrinsic threshold for initiating mitochondrial-induced apoptosis, based on the balance between pro- and anti-apoptotic protein members of the BCL-2 family 5 , 14 , 20 . Bearing this in mind, we performed western blot assays to analyze the expression levels of crucial BCL-2 family members in hPSCs at 4-, 8- and 24-h post-hypoxia (1% O 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…hPSCs are very susceptible to undergo apoptosis due to their higher state of mitochondrial priming, a lowered cell intrinsic threshold for initiating mitochondrial-induced apoptosis, based on the balance between pro- and anti-apoptotic protein members of the BCL-2 family 5 , 14 , 20 . Bearing this in mind, we performed western blot assays to analyze the expression levels of crucial BCL-2 family members in hPSCs at 4-, 8- and 24-h post-hypoxia (1% O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, elucidating the mechanisms involved in hypoxia-induced apoptosis may help to control hPSC fate, and minimize cell death within hypoxic niches. To face this obstacle, we recently demonstrated that CoCl 2 , a widely used chemical surrogate of hypoxia, triggered apoptotic cell death in hPSCs via a NOXA-mediated HIF-1α and HIF-2α independent mechanism 5 . Our findings suggest that MCL-1 could regulate hPSC survival after exposure to 1% O 2 and that depending on the hypoxia inducer, alternative gene expression programs become operative in hPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations